Fostering Prevocational STEAM Learning through Motion-to-Electricity Module: A Hands-on Approach for Elementary Students - Ricky Cahyasari Putra; Ikhsanudin Ikhsanudin; Ade Dwi Putra Janata; Rusdi Febriyanto; Ananda Yhuto Wibisono Putra (International Journal of STEM Education for Sustainability, 2026)
The inclusion of Science, Technology, Engineering, Arts, and Mathematics (STEAM) education in the elementary level has been seen as a crucial part in the development of 21st-century skills and prevocational developments of elementary students. This study aims to find out the effectiveness of a hands-on motion-to-electricity learning module in enhancing STEAM skills of 5th-grade elementary students using a one-shot quasi-experimental design. The participants consisted of 28 fifth-grade students from a primary school in the Banten province. To demonstrate the conversion of kinetic energy into electrical energy, the students built simple wheel generator sets using bicycle dynamos, wires, rotating wheels, and LED lights. Immediately after the activity, a 15-item validated evaluation form was employed to collect data, focusing on the principles of energy conversion, concepts of renewable energy, and simple engineering knowledge. Based on the statistical analysis, 82.1% of the students achieved beyond the required level of proficiency, scoring a mean of 67.25 and a standard deviation of 16.34. The findings of the observation conclusion revealed that the students exhibited a positive attitude towards technical subjects, were actively engaged in their learning process, and worked together to overcome problems. The findings of the study's conclusion indicate that interactive STEAM educational materials can be a valuable tool in increasing the interest of primary school students in technical subjects and their understanding of energy conversion concepts. This study supports the use of hands-on learning approaches in elementary STEAM education as a foundation for future prevocational and technical education.